The Utilization of Social Media in Islamic Education - Amir, Afriandi; Waddah, Ilma; Maskadilah, Andi; Yunita, Misra; Anrang, Musfir; Putra, Muhammad Farhan; Ismi, Nur (State Islamic Institute of Bone, Indonesia, 2024)
The development of the digital age has changed people's lifestyles including in the domain of Islamic Religious Education. Social media has a significant role in the learning process, facilitating access to information, interaction, and collaboration between learners. The utilization of social media as a learning tool for Islamic Education is in accordance with the principles of the 2013 curriculum, where learners play an active role in the learning process. Although it provides great benefits, the use of social media also poses challenges, including the spread of false information that can affect learners' religious understanding and beliefs. Therefore, it is necessary to improve critical skills in verifying the truth of information on social media platforms. This research uses the literature review method to explore the utilization of social media in Islamic Education. The results show that social media has a positive impact on learning, but also causes negative impacts such as addiction, exposure to negative content, and disruption to learning concentration.